Correlation between profitability and changes in stock price of selected holding firms - Banquito, Georgette I. et.al. 4 0 16; 5 (2016)
u
Financial Plan : (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2